2008
DOI: 10.1158/1535-7163.mct-07-0177
|View full text |Cite
|
Sign up to set email alerts
|

Improved grading and survival prediction of human astrocytic brain tumors by artificial neural network analysis of gene expression microarray data

Abstract: Histopathologic grading of astrocytic tumors based on current WHO criteria offers a valuable but simplified representation of oncologic reality and is often insufficient to predict clinical outcome. In this study, we report a new astrocytic tumor microarray gene expression data set (n = 65). We have used a simple artificial neural network algorithm to address grading of human astrocytic tumors, derive specific transcriptional signatures from histopathologic subtypes of astrocytic tumors, and asses whether thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 31 publications
2
76
0
Order By: Relevance
“…Comparing the neoplastic cells with the normal counterpart (normal human astrocytes), we observed an increased expression of DUSP6 (three-to sixfold) at baseline that increased upon mitogenic stimulation ( Figure 1a, lower panel). Consistently, gene expression studies revealed DUSP6 upregulation (mean fold changes: 3.14) in human astrocytic brain tumors compared with normal brain tissue (Petalidis et al, 2008). All cells were serumstarved overnight and stimulated with 100 ng/ml of EGF for 3 h. Despite some fluctuation monitored, northern hybridization of non-neoplatic cells (unstimulated cultures of murine pheochromocytoma PC12 cells, mouse fibroblasts NIH-3T3 and normal human astrocytes) showed basal negligible mRNA levels and powerful induction of DUSP6 mRNA upon mitogenic stimulation ( Figure 1a, upper panel).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Comparing the neoplastic cells with the normal counterpart (normal human astrocytes), we observed an increased expression of DUSP6 (three-to sixfold) at baseline that increased upon mitogenic stimulation ( Figure 1a, lower panel). Consistently, gene expression studies revealed DUSP6 upregulation (mean fold changes: 3.14) in human astrocytic brain tumors compared with normal brain tissue (Petalidis et al, 2008). All cells were serumstarved overnight and stimulated with 100 ng/ml of EGF for 3 h. Despite some fluctuation monitored, northern hybridization of non-neoplatic cells (unstimulated cultures of murine pheochromocytoma PC12 cells, mouse fibroblasts NIH-3T3 and normal human astrocytes) showed basal negligible mRNA levels and powerful induction of DUSP6 mRNA upon mitogenic stimulation ( Figure 1a, upper panel).…”
Section: Resultssupporting
confidence: 62%
“…Interestingly, DUSP6 is a selected gene for astrocytic classification in angiogenic functional class and, recently, a potential transcriptional effect of hypoxia on the DUSP6 gene has been reported (Petalidis et al, 2008;Bermudez et al, 2011). Moreover, inducible expression of DUSP6 specifically blunts in vivo fibroblasts growth but, in our opinion, this effect probably relies on Ha-Ras oncogene transformation (Marchetti et al, 2004).…”
Section: Dusp6 Regulation and Function In Glioblastoma Cancer Cells Smentioning
confidence: 75%
“…A tumorsuppressor role of PEA-15 was proposed in brain tumors based on its decreased expression at the mRNA and protein level in GBM compared with low-grade astrocytoma with 50% of GBM nevertheless having high PEA-15 expression. 41,42 Interestingly, expression of pser116-PEA-15 was confined in specific intratumoral area with the strongest immunoreactivity in perinecrotic area. 43 Our preliminary results indicated that α5 integrin could also be localized in these particular area in GBM specimens (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…To quantify the accuracy of prediction, we utilized independent test data sets from four studies (25,26,37,38). Firstly, ensemble mortalities for each individual in the test data were computed using the random survival forests model fitted to our data set with selected genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, microarray technology has permitted development of multi-organ cancer classification including gliomas (4-6), identification of glioma subclasses (7)(8)(9)(10)(11)(12)(13)(14)(15), discovery of molecular markers (16)(17)(18)(19)(20)(21)(22)(23) and prediction of disease outcomes (24)(25)(26)(27). Unlike clinicopathological staging, molecular staging can predict long-term outcomes of any individual based on the gene expression profile of the tumor at diagnosis, helping clinicians make an optimal clinical decisions.…”
Section: Introductionmentioning
confidence: 99%